Antibody responses in buffalos immunized with Clostridium perfringens beta and epsilon toxoids - S. M Rahman; K. B Baek; T. S Hong; H. J Lee (Veterinární Medicína, 2001)
The antibody responses to toxoids were measured to investigate whether Clostridium perfringens beta and epsilon toxoids induced protective humoral immune responses in buffalos. Total of 24 buffalos were divided into 4 groups (n = 6), beta toxoid, epsilon toxoid, combination and control groups. These buffalo groups were administered each of the designated toxoids. Immunizations in the beta and epsilon toxoid groups induced strong antibody responses. The neutralizing antibody titres from the beta and epsilon toxoid groups were equally log101.2 on day 21 after inoculation whereas there was no antibody titre detected from the control group. A statistically significant (P < 0.01) increase in antibody titre was observed from day 0 to day 14 and 21 after inoculation. The antibody production did not vary significantly due to day of inoculation and toxoid interactions.